Remembering a Location Makes the Eyes Curve Away - Theeuwes, Jan; Olivers, Christian N.L.; Chizk, Christopher L. (Psychological Science, 2005)
Working memory is a system that keeps limited information on-line for immediate access by cognitive processes. This type of active maintenance is important for everyday life activities. The present study shows that maintaining a location in spatial working memory affects the trajectories of saccadic eye movements toward visual targets, as the eyes deviate away from the remembered location. This finding provides direct evidence for a strong overlap between spatial working memory and the eye movement system. We argue that curvature is the result of the need to inhibit memory-based eye movement activity in the superior colliculus, in order to allow an accurate saccade to the visual target. Whereas previous research has shown that the eyes may deviate away from visually presented stimuli that need to be ignored, we show that the eyes also curve away from remembered stimuli.